Os acordos de Roboré e o pensamento geopolítico brasileiro - Lemos, Walter Gustavo da Silva (2015)
This study correlates the Robore Agreements with the Brazilian geopolitical thought. As such, it aims to describe how what is written in such agreements is influenced by the thought described by geopoliticians, not only through the thought described by international schools, but also through the one supported in the country for the bilateral relations between Brazil and Bolivia. Accordingly, it aims to figure out how the Brazilian geopolitical thought influenced the goals of the Robore Agreements, starting from an approach of their economic, political, energetic, historical and military aspects as well as the physical integration promoted by the Agreements. This was done through a bibliographical research on the scholars of the Brazilian geopolitics and the Brazilian government’s diplomatic and political performances regarding Bolivia and such treaties. For the study, the analysis of the historical antecedents of the governmental relations between Brazil and Bolivia was necessary as a mean to comprehend the circumstances prior to signing the Agreements. As such, it was possible to develop a study on the Brazilian geopolitical thought, concerning the issues of the international affairs with neighbouring countries, with emphasis on the relations with Bolivia. All ends with the analysis of the Robore Agreements according to the geopolitical thought in order to find out elements in the Agreements which demonstrate that the governmental diplomatic performance in the production of such agreements originated from these thoughts, especially from Mario Travassos’s (1938) masterpiece: “The Continental Projection of Brazil”.